2001
DOI: 10.1083/jcb.152.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Voltage-Dependent Anion Channel in Various Forms of Apoptosis in Mammalian Cells

Abstract: Through direct interaction with the voltage-dependent anion channel (VDAC), proapoptotic members of the Bcl-2 family such as Bax and Bak induce apoptogenic cytochrome c release in isolated mitochondria, whereas BH3-only proteins such as Bid and Bik do not directly target the VDAC to induce cytochrome c release. To investigate the biological significance of the VDAC for apoptosis in mammalian cells, we produced two kinds of anti-VDAC antibodies that inhibited VDAC activity. In isolated mitochondria, these antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
297
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(310 citation statements)
references
References 52 publications
9
297
0
4
Order By: Relevance
“…Previous work has suggested that VDAC2 would act as an endogenous inhibitor of Bak (but not Bax) (Cheng et al, 2003), whereas other VDAC isoforms would cooperate with Bax to promote apoptosis (Shimizu et al, 1999(Shimizu et al, , 2000a(Shimizu et al, , 2001. Our results point to a role for VDAC1 as an activator of Bax (but not Bak).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous work has suggested that VDAC2 would act as an endogenous inhibitor of Bak (but not Bax) (Cheng et al, 2003), whereas other VDAC isoforms would cooperate with Bax to promote apoptosis (Shimizu et al, 1999(Shimizu et al, , 2000a(Shimizu et al, , 2001. Our results point to a role for VDAC1 as an activator of Bax (but not Bak).…”
Section: Discussionsupporting
confidence: 59%
“…Although several studies have insisted on the fact that Bax/Bak-mediated MMP and PTPC-dependent MMP would occur in a completely independent, mechanistically distinct fashion, other reports suggest that proteins from the Bcl-2 family can functionally and physically interact with the PTPC (Marzo et al, 1998;Brenner et al, 2000;Belzacq et al, 2002). In this context, it has been suggested that VDAC2 would exert antiapoptotic functions by sequestering Bak (Cheng et al, 2003;Chandra et al, 2005) whereas other VDAC isoforms (possibly VDAC1 and VDAC3) would interact cooperatively with Bax to induce apoptosis (Shimizu et al, 1999(Shimizu et al, , 2001. Recently, one study performed on genetically manipulated mouse cells purported that none of the VDAC isoforms would be required for apoptotic MMP (Baines et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…42 The oligomerized Bax and Bak may form a pore for apoptogenic proteins, or may interact with the mitochondrial outer membrane voltagedependent anion channel (VDAC) to induce a change of VDAC permeability to allow apoptogenic proteins to pass through. 43 However, the mechanism of Bax-induced cytochrome c release from the mitochondria is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory action of BAX on VDAC is further demonstrated by the use of a VDAC-disrupted yeast strain that shows no Cyt c release upon BAX expression [20,24]. Furthermore BAX induced Cyt c release can be blocked by specific anti-VDAC antibodies [25], or by a VDAC inhibitor [26]. Interestingly, it was reported that tBID does not have an effect on the function of VDAC [27].…”
Section: The Involvement Of Vdac In Apoptosismentioning
confidence: 99%